Prevalence of extended-spectrum beta-lactamase and molecular detection of blaTEM, blaSHV, and blaCTX-M genotypes among gram-negative Bacilli isolates from hospital acquired infections in pediatrics, one institutional study - Ahmed Gomaa Ahmed Elsayed; Dina F. Badr; Nermene Youssef Abo El Kheir; Maysaa El Sayed Zaki; Abdelrahman Eid Mahmoud Mossad; Ehab Mohammed Fahmy Mahmoud (BMC, 2024)
Abstract Background Gram-negative bacilli represents an important pathogen in hospital-acquired infections (HAIs) worldwide. The emergence of antibiotic resistance in these pathogens warrants attention for the proper management of infections. Extended-spectrum beta-lactamase (ESBL) resistance represents a major therapeutic problem in infections due to Gram-negative bacilli. The present study aimed to study the extended-spectrum beta-lactamase genes blaTEM, blaSHV, and blaCTX-M by multiplex polymerase reaction in isolated Gram-negative bacilli from HAIs in pediatric patients. Methods The study included one hundred-five isolates of Gram-negative bacilli from pediatric patients with different types of HAIs. The isolates were subjected to full microbiological identification, antibiotics susceptibility by disc diffusion method, the phenotypic study of ESBL, and the genetic study of ESBL genes by multiplex PCR. Results Fifty isolates of Gram-Negative bacilli showed ESBL activity by a phenotypic study by double disc diffusion method (50/105). All ESBL producers' isolates were positive by PCR for ESBL genes. The most frequent gene was blaTEM (64%), followed by blaSHV (30%) and CTX-M (22%). Mixed genes were found in 4 isolates (8%) for blaTEM and blaSHV, blaTEM and CTX-M. There was a significant association between PCR for ESBL genes and phenotypic ESBL detection (P = 0.001). There was significant detection of ESBL genes in E. coli (28%), followed by Enterobacter spp. (26%), Klebsiella spp. (24%), Serratia (14%), Pseudomonas spp. (6%) and Proteus (2%), P = 0.01. There Seventy percent of isolates positive for ESBL production had an insignificant association between MDR and PCR for ESBL genes (P = 0.23). Conclusion The present study highlights the prevalence of ESBL activity among clinical isolates of Gram-negative bacilli isolated from hospital-acquired infections in pediatric patients. The most common gene responsible for this activity was blaTEM gee followed by blaSHV and blaCTX-M. There was a high prevalence of multiple antibiotic resistance among isolates with ESBL activity. The finding of the present study denotes the importance of screening extended beta-lactamase among Gram-negative bacilli associated with HAIs in pediatric patients.